Abrasive material with core coating structure as well as preparation method and application of abrasive material

By spraying and curing the shell slurry of cubic boron nitride on the surface of silicon carbide to form abrasive with a core-covered structure, the problem of low utilization efficiency of micro-nano cubic boron nitride in abrasives is solved, and abrasive preparation with high wear resistance, large size and high thermal stability is achieved.

CN119875585APending Publication Date: 2025-04-25SHENHUA RAIL & FREIGHT WAGONS TRANSPORT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411789828.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use micro-nano cubic boron nitride to produce high-performance abrasives, and the uniformity and bonding strength of the composite abrasives are relatively poor.

Method used

Using abrasive preparation method with a core-covered structure, the shell slurry of cubic boron nitride is cured on the surface of silicon carbide to form an abrasive with high wear resistance, large size and high thermal stability.

Benefits of technology

The use of small-particle cubic boron nitride to produce ultra-hard large-size abrasives is achieved, which improves the bonding strength and uniformity of the abrasives, solves the problem of nano-scale fine abrasives inventory, and enhances the market value of silicon carbide abrasives.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an abrasive material with a core-coated structure as well as a preparation method and application thereof. The abrasive material comprises an abrasive material component with a core-coated structure which takes silicon carbide as a core, micro-nano cubic boron nitride as a shell and sodium silicate as an adhesive, the grinding material has the characteristics of high wear resistance, large size and high thermal stability. The preparation method comprises the following steps: (1) preparing shell slurry: mixing a curing agent, an adhesive solution and shell raw materials of cubic boron nitride, and pulping to obtain the shell slurry; and (2) grinding material forming: spraying the shell slurry obtained in the step (1) on the surface of silicon carbide, and carrying out curing treatment. By adopting the method disclosed by the invention, the superhard large-size grinding material can be manufactured by using the small-particle-size cubic boron nitride, the inventory problem of nanoscale fine grinding materials of cubic boron nitride manufacturing enterprises is effectively solved, and meanwhile, the market value of the silicon carbide grinding material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of superhard materials, and in particular is an abrasive with a core-coated structure and a preparation method and application thereof. Background Art

[0002] With the rapid development of technologies in the fields of electronic technology and rail transportation, as well as the continuous emergence of various new materials, the requirements for workpiece processing accuracy in various fields are getting higher and higher, and the demand for high-precision processing abrasives is increasing. Therefore, as the core material of high-precision processing abrasives, the research and development of high-wear-resistant abrasives has become a hot topic in the current abrasive field. High-precision, high-efficiency, low-pollution, and low-cost processing methods have become a new development trend in the manufacturing industry, and this development trend is inseparable from the application of high-performance grinding tools.

[0003] Cubic boron nitride has excellent properties such as high hardness, high chemical stability, high wear resistance and low friction coefficient, but its high price limits its large-scale use. Due to its small size, micro-nano cubic boron nitride has low grinding efficiency in practical applications and it is difficult to prepare high-performance grinding tools. In order to improve the utilization rate of micro-nano cubic boron nitride and produce high-wear-resistant abrasives, the prior art also discloses some methods, such as:

[0004] Patent CN104293291B discloses a superhard composite abrasive and a preparation method thereof, wherein the superhard composite abrasive is composed of the following components in weight percentage: 10% to 90% of cubic boron nitride and / or diamond, and 10% to 90% of additives; wherein the additives are any one of oxides, nitrides, carbides, carbonitrides, nitride aluminum compounds, garnets, and doped metals, or any combination thereof. The superhard composite abrasive of the present invention is compounded with cubic boron nitride and / or diamond and any one of oxides, nitrides, carbides, carbonitrides, nitride aluminum compounds, garnets, and doped metals, or any combination thereof, and the resulting composite abrasive has high hardness and toughness, strong grinding ability, and high efficiency; it has good wear resistance, thermal stability, and chemical stability, and has a long service life; at the same time, the use of the abrasive during processing generates less dust, thereby avoiding pollution to the ambient air; it is suitable for metal cutting, grinding, and other processing processes. However, the uniformity and bonding strength of this composite abrasive are relatively poor.

[0005] Patent application CN116922280A discloses a cubic boron nitride composite abrasive, which is mainly composed of corundum, nano cubic boron nitride and nano corundum coated with a ceramic binder, wherein the nano cubic boron nitride and nano corundum are bonded to the surface of the corundum by a ceramic binder. The present invention also provides a method for preparing the above-mentioned boron nitride composite abrasive, comprising the following steps: pretreatment of nano cubic boron nitride and nano corundum, sol-gel treatment, forming a cubic boron nitride coated corundum composite blank powder, and sintering the composite blank powder. The present invention prepares a ceramic binder on the surface of uniformly dispersed nano cubic boron nitride and nano corundum by sol-gel technology, prepares the prepared composite powder into slurry, uses a high-pressure spray gun to adhere the composite powder to the surface of the corundum to obtain a cubic boron nitride composite blank powder, and sinters the composite powder to obtain a cubic boron nitride composite abrasive. The composite abrasive provided by the invention has good wear resistance. However, the composite abrasive coating layer includes two abrasives, which easily leads to uneven quality of the coating layer, and the final sintering operation may affect the performance of the material.

[0006] Patent application CN117821015A discloses a thermally stable multi-layer core-shell structure superhard composite abrasive and a preparation method thereof, and relates to the field of superhard material technology. The thermally stable multi-layer core-shell structure superhard composite abrasive provided by the present invention comprises diamond particles and a cubic boron nitride layer and a diamond layer wrapped outside the diamond particles. The diamond particles are used as the core, and the cubic boron nitride layer and the diamond layer are alternately wrapped outside in sequence. The alternating layers of core-shell structure, on the one hand, make the shortcomings of diamond and cubic boron nitride in performance during grinding mutually compensate for each other, and on the other hand, can make the combination of diamond and cubic boron nitride more firmly. The composite abrasive has higher quality stability and can be applied to the field of precision grinding. However, this alternating layer-by-layer structure has the problem of uneven bonding in practical applications, and the preparation process is complicated and the cost is high.

[0007] Therefore, there is an urgent need to provide a method for producing a highly wear-resistant abrasive using micro-nano cubic boron nitride in a simple process. Summary of the invention

[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an abrasive with a core-coated structure and a preparation method and application thereof; the abrasive of the present invention has the characteristics of high wear resistance, large size and high thermal stability; the method of the present invention can be used to manufacture ultra-hard large-size abrasives using small-particle cubic boron nitride, effectively solving the inventory problem of nano-grade fine abrasives of cubic boron nitride manufacturing companies, and at the same time improving the market value of silicon carbide abrasives.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing an abrasive having a core-coated structure, the preparation method comprising the following steps:

[0011] (1) Preparation of shell slurry: mixing and slurrying shell raw materials including a curing agent, an adhesive solution and cubic boron nitride to obtain a shell slurry;

[0012] (2) Abrasive forming: The shell slurry obtained in step (1) is sprayed on the surface of silicon carbide and cured.

[0013] In some embodiments of the present invention, the particle size of the cubic boron nitride is 20 to 100 nm, preferably 20 to 60 nm, and more preferably 30 to 50 nm.

[0014] In some embodiments of the present invention, the particle size of the silicon carbide is 500-700 μm.

[0015] In some embodiments of the present invention, in step (1), the curing agent is selected from MgO and / or CaO.

[0016] In some embodiments of the present invention, the adhesive solution is selected from a sodium silicate solution having a modulus of 3.3 to 3.5 and a mass fraction of 30% to 40%, preferably an aqueous solution of sodium silicate.

[0017] In some embodiments of the present invention, the adhesive solution is selected from a polyvinyl alcohol (PVA) solution with a modulus of 3.3 to 3.5 and a mass fraction of 30% to 40%, preferably an aqueous solution of PVA.

[0018] Sodium silicate is an inorganic adhesive. Compared with traditional organic adhesives, it has better thermal conductivity and better thermal stability than organic adhesives. Since abrasives generate a lot of friction heat during grinding, the thermal conductivity and thermal stability of abrasives are very important. Using sodium silicate as an adhesive can improve the thermal conductivity and thermal stability of abrasives, making the comprehensive performance of the prepared abrasives even better.

[0019] In some embodiments of the present invention, the amount of the curing agent is 2% to 4% by mass of the adhesive solution.

[0020] In some embodiments of the present invention, the mixing mass ratio of the adhesive solution to cubic boron nitride is (3-5):1.

[0021] In some embodiments of the present invention, the mixing and slurrying is carried out under stirring; preferably, the stirring speed is 400-800 r / min; more preferably, the stirring treatment time is 40-90 min, and / or the treatment temperature is 50-60°C.

[0022] In some embodiments of the present invention, the mixing and slurrying are carried out under ultrasound and stirring; preferably, the frequency of the ultrasound is 80-120KHz, and / or the speed of the stirring is 400-600r / min; more preferably, the time of the ultrasound and stirring treatment is 40-60min, and / or the treatment temperature is 50-60°C; further preferably, the ultrasound and stirring are carried out in an ultrasonic mechanical stirring equipment.

[0023] When mixing and slurrying are carried out under ultrasound and stirring, ultrasound can generate tiny bubbles, which will produce strong local shear force when they burst, helping to break up the aggregation between particles and make the particles more evenly dispersed in the solution. Stirring can provide a macroscopic mixing effect, and the combination of ultrasound and stirring can achieve microscopic and macroscopic mixing effects and improve mixing uniformity.

[0024] In some embodiments of the present invention, in step (2), the spraying is performed using a spray device; preferably, during the spraying process, the caliber of the spray device is set to 50-100 μm, and the spraying pressure is set to 0.4-1.0 MPa.

[0025] In some embodiments of the present invention, in step (2), the silicon carbide is placed in a moving state while the shell slurry is sprayed on the silicon carbide so that the shell slurry is more evenly attached to the surface of the silicon carbide; preferably, the silicon carbide is placed in a vibrating device such as a vibrating screen and the vibration mode is turned on to put the silicon carbide in a moving and flippable state.

[0026] In some embodiments of the present invention, in the step (2), the spraying is performed at a temperature of 20 to 90°C, preferably, at a temperature of 30 to 80°C.

[0027] In some embodiments of the present invention, the curing process includes a pre-curing process and a high temperature curing process performed sequentially.

[0028] In some embodiments of the present invention, the pre-curing treatment is performed at 90-120°C.

[0029] In some embodiments of the present invention, during the pre-curing process, the abrasive to be pre-cured is placed in a moving and flippable state to avoid the abrasive particles from sticking together, which is also beneficial to improving the uniformity of curing and obtaining a large-sized abrasive with a micro-nano cubic boron nitride abrasive layer evenly coated on the surface.

[0030] In some specific embodiments of the present invention, a vibrating device such as a vibrator is installed at the bottom of a curing device used for pre-curing treatment to put the abrasive to be pre-cured in a moving and flippable state.

[0031] In some specific embodiments of the present invention, the abrasive to be pre-cured is placed in a movable and flippable state by installing a stirring device such as a stirrer inside a curing device used for pre-curing.

[0032] In some embodiments of the present invention, the high temperature curing treatment is performed at 300-500°C.

[0033] In some embodiments of the present invention, the spraying and pre-curing steps are performed in batches; preferably, the spraying and pre-curing operations are repeated 2 to 5 times in sequence during the entire abrasive forming process, and the pre-cured product is subjected to high-temperature curing after the last pre-curing treatment.

[0034] In some embodiments of the present invention, the preparation method further comprises pretreating the silicon carbide surface before performing step (2), wherein the pretreatment comprises any one of surface cleaning treatment and surface modification treatment or the surface cleaning treatment and surface modification treatment performed sequentially.

[0035] In some embodiments of the present invention, the surface cleaning treatment of silicon carbide includes any one of acid cleaning and alkali cleaning or acid cleaning and alkali cleaning performed sequentially.

[0036] In some embodiments of the present invention, the pickling of silicon carbide is carried out in a 0.5-1.5 mol / L nitric acid solution, a 0.5-1.5 mol / L hydrochloric acid solution or a 5-15 mol / L hydrofluoric acid solution; preferably, the pickling time is 10-30 min; more preferably, the pickling process is accompanied by ultrasonic oscillation treatment; further preferably, the frequency of the ultrasonic wave is 28-40 kHz.

[0037] In some embodiments of the present invention, the alkali washing of silicon carbide is carried out in a sodium hydroxide solution with a concentration of 0.5 to 1.5 mol / L or a potassium hydroxide solution with a concentration of 0.5 to 1.5 mol / L; preferably, the alkali washing time is 10 to 30 min; more preferably, the alkali washing process is accompanied by ultrasonic oscillation treatment; further preferably, the frequency of the ultrasonic wave is 28 to 40 kHz.

[0038] In some embodiments of the present invention, the surface modification treatment of silicon carbide comprises mixing anhydrous ethanol, a surfactant and silicon carbide or silicon carbide that has been surface cleaned, and reacting the mixture at 60 to 80° C. for 40 to 60 minutes; preferably, the mixing mass ratio of the anhydrous ethanol, the surfactant and the silicon carbide is (100 to 800): (1 to 3): 100, and / or the surfactant is selected from at least one of cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), polyethylene glycol (PEG), cocamidopropyl betaine (CAPB) and the like.

[0039] In some embodiments of the present invention, the silicon carbide that has been surface cleaned is silicon carbide that has been surface cleaned and dried; preferably, the drying conditions include: a temperature of 80 to 90° C., and / or a drying time of 1 to 3 hours.

[0040] In some embodiments of the present invention, the surface-cleaned silicon carbide is silicon carbide that is surface-cleaned, rinsed to neutrality, and then dried; preferably, the drying conditions include: a temperature of 80 to 90° C., and / or a drying time of 1 to 3 hours.

[0041] In some embodiments of the present invention, the surface modification of silicon carbide is performed during stirring; preferably, the stirring speed is 300-800 rpm.

[0042] In the present invention, surface cleaning treatment of silicon carbide can remove impurities on the surface of silicon carbide, especially when the surface of silicon carbide is acid-washed and alkaline-washed in sequence, acid-washing can remove the oxide layer and inorganic pollutants on the surface of silicon carbide, and alkaline washing can further remove grease and organic pollutants on the surface of silicon carbide.

[0043] In the present invention, the surface modification treatment of silicon carbide can enhance the charge on the surface of silicon carbide or improve the wettability of the surface of silicon carbide, thereby improving the bonding strength between the surface of silicon carbide and the shell slurry.

[0044] In some embodiments of the present invention, the preparation method further comprises pretreating the surface of the cubic boron nitride before performing step (1), wherein the pretreatment comprises any one of a surface cleaning treatment and a surface modification treatment or a surface cleaning treatment and a surface modification treatment performed sequentially.

[0045] In some embodiments of the present invention, the surface cleaning treatment of cubic boron nitride includes any one of acid washing and alkali washing or the acid washing and alkali washing performed sequentially.

[0046] In some embodiments of the present invention, the pickling of cubic boron nitride is carried out in a 0.5-1.5 mol / L nitric acid solution, a 0.5-1.5 mol / L hydrochloric acid solution or a 5-15 mol / L hydrofluoric acid solution; preferably, the pickling time is 10-30 min; more preferably, the pickling process is accompanied by ultrasonic oscillation treatment; further preferably, the frequency of the ultrasonic wave is 28-40 kHz.

[0047] In some embodiments of the present invention, the alkali washing of cubic boron nitride is carried out in a sodium hydroxide solution with a concentration of 0.5 to 1.5 mol / L or a potassium hydroxide solution with a concentration of 0.5 to 1.5 mol / L; preferably, the alkali washing time is 10 to 30 min; more preferably, the alkali washing process is accompanied by ultrasonic oscillation treatment; further preferably, the frequency of the ultrasonic wave is 28 to 40 kHz.

[0048] In some embodiments of the present invention, the surface modification treatment of cubic boron nitride comprises mixing anhydrous ethanol, a surfactant and cubic boron nitride or cubic boron nitride after surface cleaning, and reacting the mixture at 60 to 80° C. for 40 to 60 minutes; preferably, the mixing mass ratio of the anhydrous ethanol, the surfactant and the cubic boron nitride is (80 to 120): (1 to 3): 100, and / or the surfactant is selected from at least one of hexadecyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), polyethylene glycol (PEG) and the like.

[0049] In some embodiments of the present invention, the surface-cleaned cubic boron nitride is surface-cleaned and dried cubic boron nitride; preferably, the drying conditions include: a temperature of 80 to 90° C., and / or a drying time of 1 to 3 hours.

[0050] In some embodiments of the present invention, the surface-cleaned cubic boron nitride is cubic boron nitride that is surface-cleaned, rinsed to neutrality, and then dried; preferably, the drying conditions include: a temperature of 80 to 90° C., and / or a drying time of 1 to 3 hours.

[0051] In some embodiments of the present invention, the surface modification of cubic boron nitride is performed during stirring; preferably, the stirring speed is 100 to 500 rpm, preferably 200 to 400 rpm.

[0052] In the present invention, the surface cleaning treatment of cubic boron nitride can remove impurities on the surface of cubic boron nitride, especially when the surface of cubic boron nitride is acid-washed and alkaline-washed in sequence, the acid-washing can remove the oxide layer and inorganic pollutants on the surface of cubic boron nitride, and the alkaline-washing can further remove grease and organic pollutants on the surface of cubic boron nitride.

[0053] In the present invention, surface modification treatment is performed on cubic boron nitride to improve the dispersibility of cubic boron nitride and enhance the charge on the surface of cubic boron nitride or improve the wettability of the surface of cubic boron nitride, thereby improving the dispersibility of cubic boron nitride in the shell slurry and the bonding strength between cubic boron nitride and silicon carbide in the shell slurry.

[0054] In some embodiments of the present invention, the preparation method comprises the following steps:

[0055] (1) Surface cleaning treatment: acid washing and alkali washing are performed on silicon carbide and cubic boron nitride respectively; preferably, silicon carbide and cubic boron nitride are dried respectively after alkali washing; more preferably, the drying conditions include a temperature of 80 to 90° C. and a time of 1 to 3 hours;

[0056] (2) Surface modification: The silicon carbide and cubic boron nitride that have been surface cleaned are dispersed in anhydrous ethanol and a surfactant is added to perform surface modification. Preferably, the silicon carbide and cubic boron nitride are dried after the surface modification. More preferably, the drying conditions include a temperature of 80 to 90° C. and a time of 1 to 3 hours.

[0057] (3) Preparation of shell slurry: mixing the curing agent, the adhesive solution and the surface-modified cubic boron nitride obtained in step (2) and slurrying to obtain shell slurry; preferably, the adhesive solution is selected from a sodium silicate aqueous solution with a modulus of 3.3 to 3.5 and a mass fraction of 30% to 40%;

[0058] (4) Abrasive forming: spraying the shell slurry obtained in step (3) onto the surface of the surface-modified silicon carbide obtained in step (2) and performing a curing treatment; preferably, the curing treatment includes a pre-curing treatment and a high-temperature curing treatment performed in sequence; more preferably, the pre-curing treatment is performed at 90 to 120° C., and the high-temperature curing treatment is performed at 300 to 500° C.

[0059] In a second aspect, the present invention provides the application of the preparation method described in the first aspect in the production of superhard materials, especially in the production of precision grinding tools.

[0060] In a third aspect, the present invention provides an abrasive, comprising an abrasive component having a core-wrapped structure with silicon carbide as a core, micro-nano cubic boron nitride as a shell, and sodium silicate as a binder.

[0061] In some embodiments of the present invention, the particle size of the silicon carbide is 500-700 μm.

[0062] In some embodiments of the present invention, the shell layer has a thickness of 5 to 20 μm.

[0063] In some embodiments of the present invention, the abrasive component is prepared by the preparation method described in the first aspect.

[0064] In a fourth aspect, the present invention provides the use of the abrasive described in the third aspect in the production of superhard materials, especially in the production of precision grinding tools.

[0065] The beneficial effects of the present invention are as follows:

[0066] The abrasive of the present invention uses silicon carbide as a core. Although the hardness and wear resistance of silicon carbide abrasive are lower than those of cubic boron nitride, silicon carbide has higher thermal stability and lower price, which can effectively improve the thermal stability of the abrasive and reduce the cost of the abrasive. The abrasive of the present invention uses micro-nano-scale cubic boron nitride as a shell layer. Cubic boron nitride has higher hardness and better wear resistance, and can meet the requirements of general abrasive tools for hardness and wear resistance.

[0067] The present invention proposes a method for preparing an abrasive with a core-coated structure by spraying and curing silicon carbide with a shell slurry containing cubic boron nitride. The method is simple to operate and is conducive to industrial production. The prepared abrasive has the characteristics of high wear resistance, large size and high thermal stability. The method of the present invention can be used to manufacture ultra-hard large-size abrasives using small-particle cubic boron nitride, effectively solving the inventory problem of nano-level fine abrasives of cubic boron nitride manufacturing companies and improving the market value of silicon carbide abrasives. DETAILED DESCRIPTION

[0068] The following examples further illustrate the technology of the present invention. These examples are for illustration and example of the present invention and are not intended to limit the scope of the present invention in any form.

[0069] Example 1

[0070] A method for preparing an abrasive having a core-coated structure, the method comprising the following steps:

[0071] (1) Surface cleaning:

[0072] 1-1) The cubic boron nitride with a particle size of 20 nm is acid-washed in a nitric acid solution with a concentration of 1 mol / L and subjected to ultrasonic vibration at 32 kHz for 10 min, and filtered; the acid-washed cubic boron nitride is then alkali-washed in a NaOH solution with a concentration of 1 mol / L and subjected to ultrasonic vibration at 32 kHz for 10 min, and filtered; the alkali-washed cubic boron nitride is then rinsed with distilled water until it is neutral; finally, the cubic boron nitride is dried in a vacuum drying oven at a temperature of 80° C. for 1 h, and packaged for later use.

[0073] 1-2) The silicon carbide with a particle size of 500 μm is acid-washed in a nitric acid solution with a concentration of 1 mol / L and ultrasonically vibrated at 32 kHz for 10 min, and filtered; the acid-washed silicon carbide is then alkaline-washed in a NaOH solution with a concentration of 1 mol / L and ultrasonically vibrated at 32 kHz for 10 min, and filtered; the alkaline-washed silicon carbide is then rinsed with distilled water until it is neutral; finally, the silicon carbide is dried in a vacuum drying oven at a temperature of 80° C. for 1 h, and packaged for later use.

[0074] There is no order of precedence for the above steps 1-1) and 1-2), and they can be performed simultaneously, or any one of them can be performed first.

[0075] (2) Surface modification:

[0076] 2-1) adding the cubic boron nitride after the surface cleaning treatment in step 1-1) to anhydrous ethanol and adding hexadecyltrimethylammonium bromide, wherein the mass ratio of anhydrous ethanol, hexadecyltrimethylammonium bromide to cubic boron nitride is 80:1:100; then stirring at 100 rpm for 40 minutes at 60° C. in a water bath heating magnetic stirrer, filtering, and then drying the cubic boron nitride in a vacuum drying oven at 80° C. for 1 hour, and packaging for standby use.

[0077] 2-2) adding the silicon carbide after the surface cleaning treatment in step 1-2) to anhydrous ethanol and adding cetyltrimethylammonium bromide, wherein the mass ratio of anhydrous ethanol, cetyltrimethylammonium bromide and silicon carbide is 80:1:100; then stirring at 300 rpm for 40 minutes at 60°C in a water bath heating magnetic stirrer, filtering, and then drying the silicon carbide at 80°C for 1 hour in a vacuum drying oven, and packaging for later use.

[0078] There is no order of precedence for the above steps 2-1) and 2-2), and they can be performed simultaneously, or any one of them can be performed first.

[0079] (3) Shell slurry preparation:

[0080] 3-1) Take a certain mass of sodium silicate aqueous solution with a modulus of 3.3 and a mass fraction of 30%, add MgO at a rate of 2% of the mass of the sodium silicate aqueous solution, and stir magnetically for 60 minutes to fully mix MgO and the sodium silicate aqueous solution.

[0081] 3-2) taking a certain mass of cubic boron nitride obtained in step 2-1), mixing the cubic boron nitride with the mixed solution obtained in step 3-1) at a mass ratio of cubic boron nitride to sodium silicate aqueous solution of 1:3, and treating in an ultrasonic mechanical stirring device at a frequency of 80 KHz and a rotation speed of 400 r / min for 40 minutes at a temperature of 50°C.

[0082] (4) Abrasive forming:

[0083] 4-1) The silicon carbide obtained in step 2-2) is spread on a vibrating screen with a mesh size of 32 meshes, and the shell slurry obtained in step 3-2) is loaded into a spray device.

[0084] 4-2) Start the curing equipment set under the vibrating screen and set the temperature to 90°C. When the temperature rises to 90°C, start the spray equipment and spray the shell slurry in the spray equipment on the silicon carbide surface in the vibrating screen in the form of small droplets. At the same time, start the vibrating screen and the vibrator at the bottom of the curing equipment. The spray diameter of the spray equipment is set to 50μm, the spray pressure is set to 0.4MPa, the vibration frequency of the vibrating screen is set to 30Hz, and the vibration frequency of the vibrator is set to 20Hz. In this step, the shell slurry sprayed out by the spray equipment adheres to the surface of silicon carbide and is initially cured on the surface of silicon carbide under the low temperature environment formed by the curing equipment. As the vibrating screen is turned on, the silicon carbide with the shell slurry initially cured on the surface is gradually shaken down into the curing equipment and further cured in the curing equipment. The vibrator set at the bottom of the curing equipment makes the silicon carbide particles in a vibrating state, which can effectively avoid the adhesion between the silicon carbide particles and improve the curing uniformity of the slurry on the surface of silicon carbide.

[0085] 4-3) After all the silicon carbide particles on the vibrating screen are shaken off into the curing device, the silicon carbide particles in the curing device are collected and spread again on a vibrating screen with a mesh size of 32, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small mist droplets, and at the same time, the shell slurry on the surface of the silicon carbide particles is cured by the curing device; thereby obtaining silicon carbide particles with the shell slurry uniformly coated on the surface.

[0086] 4-4) The silicon carbide particles obtained in step 4-3) whose surfaces are uniformly coated with the shell slurry are placed in a muffle furnace at 300°C and dried for 2 hours to finally solidify the shell slurry on the surface of the silicon carbide particles, thereby finally obtaining a core-coated structure composite abrasive having silicon carbide as a core, micro-nano cubic boron nitride as a shell, and sodium silicate as a binder.

[0087] Example 2

[0088] A method for preparing an abrasive having a core-coated structure, the method comprising the following steps:

[0089] (1) Surface cleaning:

[0090] 1-1) The cubic boron nitride with a particle size of 40 nm is acid-washed in a nitric acid solution with a concentration of 1 mol / L and subjected to ultrasonic vibration at 32 kHz for 20 min, and filtered; the acid-washed cubic boron nitride is then alkaline-washed in a NaOH solution with a concentration of 1 mol / L and subjected to ultrasonic vibration at 32 kHz for 20 min, and filtered; the alkaline-washed cubic boron nitride is then rinsed with distilled water until it is neutral; and finally, it is dried in a vacuum drying oven at a temperature of 85° C. for 2 h, and packaged for later use.

[0091] 1-2) The silicon carbide with a particle size of 600 μm is acid-washed in a nitric acid solution with a concentration of 1 mol / L and ultrasonically vibrated at 32 kHz for 20 min, and filtered; the acid-washed silicon carbide is then alkaline-washed in a NaOH solution with a concentration of 1 mol / L and ultrasonically vibrated at 32 kHz for 20 min, and filtered; the alkaline-washed silicon carbide is then rinsed with distilled water until it is neutral; and finally, it is dried in a vacuum drying oven at a temperature of 85° C. for 2 h, and packaged for use.

[0092] There is no order of precedence for the above steps 1-1) and 1-2), and they can be performed simultaneously, or any one of them can be performed first.

[0093] (2) Surface modification:

[0094] 2-1) adding the cubic boron nitride after the surface cleaning treatment in step 1-1) to anhydrous ethanol and adding hexadecyltrimethylammonium bromide, the added amount being calculated according to the mass ratio of anhydrous ethanol, hexadecyltrimethylammonium bromide and cubic boron nitride being 100:2:100; then stirring at 300 rpm for 50 min at 70° C. in a water bath heating magnetic stirrer, filtering, and then drying at 85° C. for 2 h in a vacuum drying oven, and packaging for later use.

[0095] 2-2) adding the silicon carbide after the surface cleaning treatment in step 1-2) to anhydrous ethanol and adding cetyltrimethylammonium bromide, wherein the mass ratio of anhydrous ethanol, cetyltrimethylammonium bromide and silicon carbide is 450:2:100; then stirring at 450 rpm for 50 min at 70° C. in a water bath heating magnetic stirrer, filtering, and then drying at 85° C. for 2 h in a vacuum drying oven, and packaging for later use.

[0096] There is no order of precedence for the above steps 2-1) and 2-2), and they can be performed simultaneously, or any one of them can be performed first.

[0097] (3) Shell slurry preparation:

[0098] 3-1) Take a certain mass of sodium silicate aqueous solution with a modulus of 3.4 and a mass fraction of 35%, add MgO at a rate of 3% of the mass of the sodium silicate aqueous solution, and stir magnetically for 70 minutes to fully mix MgO and the sodium silicate aqueous solution.

[0099] 3-2) taking a certain mass of cubic boron nitride obtained in step 2-1), mixing the cubic boron nitride with the mixed solution obtained in step 3-1) at a mass ratio of cubic boron nitride to sodium silicate aqueous solution of 1:4, and treating in an ultrasonic mechanical stirring device at a frequency of 100 KHz and a rotation speed of 500 r / min for 50 min at a temperature of 55° C.

[0100] (4) Abrasive forming:

[0101] 4-1) The silicon carbide obtained in step 2-2) is spread on a vibrating screen with a mesh size of 28 meshes, and the shell slurry obtained in step 3-2) is loaded into a spray device.

[0102] 4-2) Start the curing equipment set under the vibrating screen and set the temperature to 110°C. When the temperature rises to 110°C, start the spray equipment and spray the shell slurry in the spray equipment on the silicon carbide surface in the vibrating screen in the form of small droplets. At the same time, start the vibrating screen and the vibrator at the bottom of the curing equipment. The spray diameter of the spray equipment is set to 70μm, the spray pressure is set to 0.7MPa, the vibration frequency of the vibrating screen is set to 35Hz, and the vibration frequency of the vibrator is set to 25Hz. In this step, the shell slurry sprayed from the spray equipment adheres to the surface of silicon carbide and is initially cured on the surface of silicon carbide under the low temperature environment formed by the curing equipment. As the vibrating screen is turned on, the silicon carbide with the shell slurry initially cured on the surface is gradually shaken down into the curing equipment and further cured in the curing equipment. The vibrator set at the bottom of the curing equipment makes the silicon carbide particles in a vibrating state, which can effectively avoid the adhesion between silicon carbide particles and improve the curing uniformity of the slurry on the surface of silicon carbide.

[0103] 4-3) After all the silicon carbide particles on the vibrating screen are shaken off into the curing device, the silicon carbide particles in the curing device are collected and the obtained silicon carbide particles are spread again on the vibrating screen with a mesh number of 28, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small droplets, and the shell slurry on the surface of the silicon carbide particles is cured by the curing device at the same time. The silicon carbide particles that have been sprayed with the shell slurry for the second time and cured are further collected and spread again on the vibrating screen with a mesh number of 28, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small droplets, and the shell slurry on the surface of the silicon carbide is cured by the curing device at the same time; thereby obtaining silicon carbide particles with a surface uniformly coated with the shell slurry.

[0104] 4-4) The silicon carbide particles obtained in step 4-3) whose surfaces are uniformly coated with the shell slurry are placed in a muffle furnace at 400°C and dried for 1.5 hours to finally solidify the shell slurry on the surface of the silicon carbide particles, thereby finally obtaining a core-coated structure composite abrasive having silicon carbide as a core, micro-nano cubic boron nitride as a shell, and sodium silicate as a binder.

[0105] Example 3

[0106] A method for preparing an abrasive having a core-coated structure, the method comprising the following steps:

[0107] (1) Surface cleaning:

[0108] 1-1) The cubic boron nitride with a particle size of 60 nm is acid-washed in a nitric acid solution with a concentration of 1 mol / L and subjected to ultrasonic vibration at 32 kHz for 30 min, and filtered; the acid-washed cubic boron nitride is then alkaline-washed in a NaOH solution with a concentration of 1 mol / L and subjected to ultrasonic vibration at 32 kHz for 30 min, and filtered; the alkaline-washed cubic boron nitride is then rinsed with distilled water until it is neutral; and finally, dried in a vacuum drying oven at a temperature of 90° C. for 3 h, and packaged for later use.

[0109] 1-2) The silicon carbide with a particle size of 700 μm is acid-washed in a nitric acid solution with a concentration of 1 mol / L and ultrasonically vibrated at 32 kHz for 30 min, and filtered; the acid-washed silicon carbide is then alkaline-washed in a NaOH solution with a concentration of 1 mol / L and ultrasonically vibrated at 32 kHz for 30 min, and filtered; the alkaline-washed silicon carbide is then rinsed with distilled water until it is neutral; and finally, it is dried in a vacuum drying oven at a temperature of 90° C. for 3 h, and packaged for use.

[0110] There is no order of precedence for the above steps 1-1) and 1-2), and they can be performed simultaneously, or any one of them can be performed first.

[0111] (2) Surface modification:

[0112] 2-1) adding the cubic boron nitride after the surface cleaning treatment in step 1-1) to anhydrous ethanol and adding hexadecyltrimethylammonium bromide, wherein the mass ratio of anhydrous ethanol, hexadecyltrimethylammonium bromide and cubic boron nitride is 120:3:100; then stirring at 500 rpm for 60 min at 80° C. in a water bath heating magnetic stirrer, filtering, and then drying at 90° C. for 3 h in a vacuum drying oven, and packaging for later use.

[0113] 2-2) adding the silicon carbide after the surface cleaning treatment in step 1-2) to anhydrous ethanol and adding cetyltrimethylammonium bromide, wherein the mass ratio of anhydrous ethanol, cetyltrimethylammonium bromide and silicon carbide is 800:3:100; then stirring at 800 rpm for 60 min at 80° C. in a water bath heating magnetic stirrer, filtering, and then drying at 90° C. for 3 h in a vacuum drying oven, and packaging for later use.

[0114] There is no order of precedence for the above steps 2-1) and 2-2), and they can be performed simultaneously, or any one of them can be performed first.

[0115] (3) Shell slurry preparation:

[0116] 3-1) Take a certain mass of sodium silicate aqueous solution with a modulus of 3.5 and a mass fraction of 40%, add MgO at a rate of 4% of the mass of the sodium silicate aqueous solution, and stir magnetically for 80 minutes to fully mix the MgO and the sodium silicate aqueous solution.

[0117] 3-2) taking a certain mass of cubic boron nitride obtained in step 2-1), mixing the cubic boron nitride with the mixed solution obtained in step 3-1) at a mass ratio of cubic boron nitride to sodium silicate aqueous solution of 1:5, and treating in an ultrasonic mechanical stirring device at a frequency of 120 KHz and a rotation speed of 600 r / min for 60 min, and the temperature during the treatment is 60° C.

[0118] (4) Abrasive forming:

[0119] 4-1) The silicon carbide obtained in step 2-2) is spread evenly on a vibrating screen with a mesh size of 24 meshes, and the shell slurry obtained in step 3-2) is loaded into a spray device.

[0120] 4-2) Start the curing equipment set under the vibrating screen and set the temperature to 120°C. When the temperature rises to 120°C, start the spray equipment and spray the shell slurry in the spray equipment on the silicon carbide surface in the vibrating screen in the form of small droplets. At the same time, start the vibrating screen and the vibrator at the bottom of the curing equipment. The spray diameter of the spray equipment is set to 100μm, the spray pressure is set to 1.0MPa, the vibration frequency of the vibrating screen is set to 40Hz, and the vibration frequency of the vibrator is set to 30Hz. In this step, the shell slurry sprayed from the spray equipment adheres to the surface of silicon carbide and is initially cured on the surface of silicon carbide under the low temperature environment formed by the curing equipment. As the vibrating screen is turned on, the silicon carbide with the shell slurry initially cured on the surface is gradually shaken down into the curing equipment and further cured in the curing equipment. The vibrator set at the bottom of the curing equipment makes the silicon carbide particles in a vibrating state, which can effectively avoid the adhesion between the silicon carbide particles and improve the curing uniformity of the slurry on the surface of silicon carbide.

[0121] 4-3) After all the silicon carbide particles on the vibrating screen are shaken off into the curing device, the silicon carbide particles in the curing device are collected and the obtained silicon carbide particles are spread again on the vibrating screen with a mesh number of 24, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small mist droplets, and the shell slurry on the surface of the silicon carbide particles is cured by the curing device at the same time. The silicon carbide particles that have been sprayed with the shell slurry for the second time and cured are further collected and spread again on the vibrating screen with a mesh number of 24, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small mist droplets, and the shell slurry on the surface of the silicon carbide is cured by the curing device at the same time. The silicon carbide particles that have been solidified after three times of spraying with the shell slurry are further collected and spread again on a vibrating screen with a mesh number of 24, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small mist droplets, and the shell slurry on the surface of the silicon carbide is solidified by a solidification device. The silicon carbide particles that have been solidified after four times of spraying with the shell slurry are further collected and spread again on a vibrating screen with a mesh number of 24, and then the shell slurry in the spray device is sprayed again on the surface of the silicon carbide particles in the vibrating screen in the form of small mist droplets, and the shell slurry on the surface of the silicon carbide is solidified by a solidification device; thereby obtaining silicon carbide particles with a uniform surface coated with the shell slurry.

[0122] 4-4) The silicon carbide particles obtained in step 4-3) whose surfaces are uniformly coated with the shell slurry are placed in a muffle furnace at 500° C. and dried for 1 hour to finally solidify the shell slurry on the surface of the silicon carbide particles, thereby finally obtaining an abrasive having a core-coated structure with silicon carbide as the core, micro-nano cubic boron nitride as the shell, and sodium silicate as the adhesive.

[0123] Example 4

[0124] The method for preparing the abrasive is the same as that of Example 2, except that the surface cleaning treatment step (1) is not performed, that is, the surface modification treatment of cubic boron nitride and silicon carbide is directly performed.

[0125] Example 5

[0126] The method for preparing the abrasive is the same as that of Example 2, except that the surface modification treatment step (2) is not performed, that is, only the surface cleaning treatment of the cubic boron nitride and silicon carbide is performed.

[0127] Example 6

[0128] The preparation method of the abrasive is the same as that of Example 2, except that the adhesive in step (3) is changed from sodium silicate to PVA, that is, step 3-1) is to take a certain mass of PVA aqueous solution with a modulus of 3.4 and a mass fraction of 35%, add MgO at 3% of the mass of the PVA aqueous solution, and magnetically stir for 70 minutes to fully mix the MgO and PVA aqueous solution; step 3-2) is to take a certain mass of cubic boron nitride obtained in step 2-1), mix the cubic boron nitride with the mixed solution obtained in step 3-1) at a mass ratio of cubic boron nitride to PVA aqueous solution of 1:4, and treat it in an ultrasonic mechanical stirring equipment with a frequency of 100KHz and a rotation speed of 500r / min for 50 minutes, and the temperature during the treatment is 55°C.

[0129] Example 7

[0130] The method for preparing the abrasive is the same as that of Example 2, except that in step 1-1), cubic boron nitride with a particle size of 100 nm is prepared.

[0131] Example 8

[0132] The method for preparing the abrasive is the same as that of Example 2, except that the high temperature curing step of step 4-4) is not performed.

[0133] The bonding strength and wear resistance of the abrasives prepared in Examples 2, 4-8 above were tested, and the surface uniformity of the abrasives was scored. The results are shown in Table 1 below:

[0134] Table 1 Abrasive properties

[0135] Bonding strength (MPa) Wear resistance (mg / h) Surface uniformity score (out of 10 points) Example 2 120 5 9 points Example 4 80 10 6 points Example 5 90 8 7 points Example 6 100 7 8 points Example 7 110 6 8 points Example 8 95 8 7 points

[0136] In Table 1, bonding strength refers to the adhesion of the cubic boron nitride coating on the silicon carbide core, which is measured using a scratch tester from CSM Instruments; wear resistance refers to the ability of abrasives to resist wear, which is measured using a Taber wear tester. The surface uniformity scoring method is to observe its coverage, particle distribution, and surface smoothness and score them separately, then calculate the average of the three scores and round them off to get the final surface uniformity score. The scoring criteria for coverage, particle distribution, and surface smoothness are as follows:

[0137] Coverage scoring criteria:

[0138] 1 point: The surface is almost completely uncovered and most areas are exposed.

[0139] 3 points: The surface coverage is uneven, with obvious exposed areas.

[0140] 5 points: The surface is evenly covered, but there are still some exposed areas.

[0141] 7 points: The surface is very evenly covered with almost no exposed areas.

[0142] 10 points: The surface is completely covered without any exposed areas.

[0143] Particle distribution scoring criteria:

[0144] 1 point: The particle distribution is extremely uneven and the aggregation phenomenon is serious.

[0145] 3 points: The particles are unevenly distributed and there is obvious aggregation.

[0146] 5 points: The particles are evenly distributed, but there is still a small amount of aggregation.

[0147] 7 points: The particles are evenly distributed with almost no aggregation.

[0148] 10 points: The particles are evenly distributed without any aggregation.

[0149] Surface smoothness scoring criteria:

[0150] 1 point: The surface is very rough, with obvious protrusions and depressions.

[0151] 3 points: The surface is relatively rough, with obvious protrusions and depressions.

[0152] 5 points: The surface is relatively smooth, but there are still a few bumps and depressions.

[0153] 7 points: The surface is very smooth with almost no bumps or depressions.

[0154] 10 points: The surface is completely smooth without any bumps or depressions.

[0155] It can be seen from Example 4 that the cubic boron nitride and silicon carbide that have not been surface cleaned have impurities on their surfaces that will reduce the bonding strength between the cubic boron nitride and silicon carbide, accelerate the wear of the abrasive, and reduce the uniformity of the abrasive surface.

[0156] It can be seen from Example 5 that when the cubic boron nitride and silicon carbide are not subjected to surface modification treatment, it is not conducive to the uniform coating of the cubic boron nitride on the surface of silicon carbide, and it also reduces the coating firmness of the cubic boron nitride on the surface of silicon carbide.

[0157] It can be seen from Example 6 that the bonding strength of PVA is not as good as that of sodium silicate, which will reduce the bonding strength between cubic boron nitride and silicon carbide, accelerate the wear of the abrasive, and reduce the uniformity of the abrasive surface.

[0158] It can be seen from Example 7 compared with Example 2 that cubic boron nitride with a larger particle size is not easy to be evenly coated on the surface of silicon carbide and is easy to fall off during the grinding process.

[0159] It can be seen from Example 8 compared with Example 2 that without the final high-temperature curing treatment, the bonding strength between the cubic boron nitride coating and silicon carbide is insufficient, the uniformity of the abrasive surface is not good, the wear resistance of the abrasive is also poor, and the cubic boron nitride coating is easily ground off.

[0160] It should be noted that the above-described embodiments are only used to explain the present invention and do not constitute any limitation of the present invention. The embodiments describe the present invention and it should be understood that the words used therein are descriptive and explanatory words, rather than limiting words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention.

Claims

1. A method for preparing an abrasive having a core-coated structure, characterized in that: The preparation method comprises the following steps: (1) Preparation of shell slurry: mixing and slurrying shell raw materials including a curing agent, an adhesive solution and cubic boron nitride to obtain a shell slurry; (2) Abrasive forming: The shell slurry obtained in step (1) is sprayed on the surface of silicon carbide and cured.

2. The preparation method according to claim 1, characterized in that: The particle size of the cubic boron nitride is 20 to 100 nm, preferably 20 to 60 nm, more preferably 30 to 50 nm; and / or The particle size of the silicon carbide is 500-700 μm.

3. The preparation method according to claim 1 or 2, characterized in that: In the step (1), the curing agent is selected from MgO and / or CaO; and / or The adhesive solution is selected from a sodium silicate solution having a modulus of 3.3 to 3.5 and a mass fraction of 30% to 40%, preferably an aqueous solution of sodium silicate; and / or The amount of the curing agent is 2% to 4% of the mass of the adhesive solution; and / or The mixing mass ratio of the adhesive solution to cubic boron nitride is (3-5):1; and / or The mixing and slurrying are carried out under ultrasound and stirring; preferably, the frequency of the ultrasound is 80-120KHz, and / or the speed of the stirring is 400-600r / min; more preferably, the time of the ultrasound and stirring treatment is 40-60min, and / or the treatment temperature is 50-60°C; further preferably, the ultrasound and stirring are carried out in an ultrasonic mechanical stirring equipment.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step (2), the spraying is performed by using a spray device; preferably, during the spraying process, the caliber of the spray device is set to 50-100 μm, and the spraying pressure is set to 0.4-1.0 MPa; and / or The curing process includes a pre-curing process and a high temperature curing process performed sequentially; preferably, The pre-curing treatment is carried out at 90-120° C., and / or the high temperature curing treatment is carried out at 300-500° C.; and / or The spraying and pre-curing steps are performed in batches; preferably, the spraying and pre-curing operations are repeated 2 to 5 times in sequence during the entire abrasive forming process, and the pre-cured product is subjected to high-temperature curing after the last pre-curing.

5. The preparation method according to any one of claims 1 to 4, further comprising pre-treating the silicon carbide surface before performing step (2), wherein the pre-treatment comprises any one of surface cleaning treatment and surface modification treatment or the surface cleaning treatment and surface modification treatment performed in sequence; preferably, The surface cleaning treatment includes any one of acid washing and alkaline washing or acid washing and alkaline washing performed in sequence; preferably, the acid washing is carried out in a nitric acid solution with a concentration of 0.5 to 1.5 mol / L, a hydrochloric acid solution with a concentration of 0.5 to 1.5 mol / L, or a hydrofluoric acid solution with a concentration of 5 to 15 mol / L, and / or the alkaline washing is carried out in a sodium hydroxide solution with a concentration of 0.5 to 1.5 mol / L or a potassium hydroxide solution with a concentration of 0.5 to 1.5 mol / L; and / or The surface modification treatment comprises mixing anhydrous ethanol, a surfactant and silicon carbide or silicon carbide that has been surface cleaned and reacting the mixture at 60 to 80° C. for 40 to 60 minutes; preferably, the mixing mass ratio of the anhydrous ethanol, the surfactant and the silicon carbide is (100 to 800): (1 to 3): 100, and / or the surfactant is selected from at least one of cetyltrimethylammonium bromide, sodium lauryl sulfate, polyethylene glycol and cocamidopropyl betaine.

6. The preparation method according to any one of claims 1 to 5, characterized in that The preparation method further comprises pre-treating the surface of the cubic boron nitride before performing step (1), wherein the pre-treatment comprises any one of a surface cleaning treatment and a surface modification treatment or a surface cleaning treatment and a surface modification treatment performed in sequence; preferably, The surface cleaning treatment includes any one of acid washing and alkaline washing or acid washing and alkaline washing performed in sequence; preferably, the acid washing is carried out in a nitric acid solution with a concentration of 0.5 to 1.5 mol / L, a hydrochloric acid solution with a concentration of 0.5 to 1.5 mol / L, or a hydrofluoric acid solution with a concentration of 5 to 15 mol / L, and / or the alkaline washing is carried out in a sodium hydroxide solution with a concentration of 0.5 to 1.5 mol / L or a potassium hydroxide solution with a concentration of 0.5 to 1.5 mol / L; and / or The surface modification treatment comprises mixing anhydrous ethanol, a surfactant and cubic boron nitride or cubic boron nitride after surface cleaning treatment, and reacting the mixture at 60-80° C. for 40-60 minutes; preferably, the mixing mass ratio of the anhydrous ethanol, the surfactant and the cubic boron nitride is (100-800):(1-3):100, and / or the surfactant is selected from at least one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate and polyethylene glycol.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) Surface cleaning treatment: acid washing and alkali washing are performed on silicon carbide and cubic boron nitride respectively; preferably, silicon carbide and cubic boron nitride are dried respectively after alkali washing; more preferably, the drying conditions include a temperature of 80 to 90° C. and a time of 1 to 3 hours; (2) Surface modification: The silicon carbide and cubic boron nitride that have been surface cleaned are dispersed in anhydrous ethanol and a surfactant is added to perform surface modification. Preferably, the silicon carbide and cubic boron nitride are dried after the surface modification. More preferably, the drying conditions include a temperature of 80 to 90° C. and a time of 1 to 3 hours. (3) Preparation of shell slurry: mixing the curing agent, the adhesive solution and the surface-modified cubic boron nitride obtained in step (2) and slurrying to obtain shell slurry; preferably, the adhesive solution is selected from a sodium silicate aqueous solution with a modulus of 3.3 to 3.5 and a mass fraction of 30% to 40%; (4) Abrasive forming: spraying the shell slurry obtained in step (3) onto the surface of the surface-modified silicon carbide obtained in step (2) and performing a curing treatment; preferably, the curing treatment includes a pre-curing treatment and a high-temperature curing treatment performed in sequence; more preferably, the pre-curing treatment is performed at 90 to 120° C., and the high-temperature curing treatment is performed at 300 to 500° C.

8. An abrasive, characterized in that: The abrasive comprises an abrasive component having a core-wrapped structure with silicon carbide as a core, micro-nano cubic boron nitride as a shell, and sodium silicate as a binder; preferably, the particle size of the silicon carbide is 500-700 μm, and / or the shell thickness of the abrasive is 5-20 μm.

9. The abrasive material according to claim 8, characterized in that The abrasive component is prepared by the preparation method according to any one of claims 1 to 7.

10. Use of the preparation method according to any one of claims 1 to 7 or the abrasive according to claim 8 or 9 in the production of superhard materials, especially in the production of precision grinding tools.

Citation Information

Patent Citations

  • A kind of superhard composite abrasive and preparation method thereof

    CN104293291B

  • Preparation method of alumina-coated hexagonal boron nitride composite powder for self-lubricating cutter material

    CN104892003A

  • Preparation method of cubic boron nitride composite abrasive and product

    CN116922280A

  • Thermostable superhard composite abrasive with multi-layer core-shell structure and preparation method of thermostable superhard composite abrasive

    CN117821015A

  • Super hard gringding apparatus with ceramic binder and its manufacture

    CN1390682A